Differentiating Risk, Uncertainty, and Related Constructs in Decision Making: A Conceptual and Mathematical Analysis - Alhabeeb, M J (Journal of Current Practice in Accounting and Finance (JCPAF), 2023)
The concepts of risk and uncertainty have long been used interchangeably, leading to confusion and undesired outcomes in decision making. Despite the extensive research in this field, the distinction between these terms and related constructs is often overlooked. In fact, a study by De Groot and Thurik (2018) revealed that 88.3% of articles did not adhere to this distinction, which has led to contaminated literature and erroneous conclusions. Thus, this paper aims to differentiate the concepts of risk and uncertainty and other related constructs, such as ambiguity and probability, in financial and managerial decision making. A conceptual and mathematical analysis is presented, supported by numerical applications. The focus is on risk, as it is directly related to the success or failure of decisions. By providing a clear understanding of these concepts, decision makers can better assess the degree of certainty, estimate the level of risk and uncertainty, and make informed decisions. This paper contributes to the literature by providing a comprehensive analysis of related constructs in decision making, which can help avoid confusion and ensure more accurate theoretical and empirical findings.